Coordination in human and primate groups - Boos, Margarete; Boos, Margarete; Kolbe, Michaela; Kappeler, Peter M.; Ellwart, Thomas (Springer eBooks., 2011)
Coordination in Human and Primate Groups presents one of the first collections of the different approaches and methods used to assess coordination processes in groups. Written by psychologists and primatologists, the book represents a broad range of coordination research fields such as social psychology, work and organizational psychology, medicine, primatology, and behavioural ecology. It is designed for researchers and practitioners interested in understanding the behavioural aspects of group coordination.